The Objectification of Muslim Women in Indonesia: The Case of Fashionable Niqab in Social Media - Puteri, Perdana Aysha (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2022)
Currently, some niqab wearers are actively expressing themselves on social media, and the niqab has become part of a fashion trend. The internet and social media enable niqab wearers to actively and freely engage in social interactions, especially on contemporary social media platforms. They differ from conventional niqab wearers, who are often depicted wearing dark-colored niqabs and utilizing online activities as an alternative means of communication due to restrictions based on their religious ideology. These new niqab wearers tend to appear in bright, fashionable colors and are active in both online and offline activities. This study employs critical discourse analysis to examine two aspects: firstly, the discourses shaping the moral and Islamic construction of women’s bodies in the Indonesian context; secondly, how the emergence of a new niqab trend relates to the discourse on women’s bodies. The findings reveal that the new niqab trend represents a shift in the meaning of the niqab from a moral identity to being associated with fashion expression now and individuality in the digital era. This research contributes to academic studies by offering a new perspective on the relationship between religion, fashion, and social media, while also enriching the discourse on Muslim women's bodies in the modern Indonesian context.